(untitled) (The Pakistan Development Review, 1977)
The policy of higher tax on petrol than on diesel gasoline encourages diesel transport. This may cause distortion and suboptimal allocation. This note is aimed at testing this hypothesis empirically. The First section briefly des¬cribes the petrol versus diesel argument. In the Second section cost compari¬sons are made for two petrol and diesel vehicles of comparable performance. The conclusion and policy options are discussed in the Third section.